How to build a business rules engine extending application functionality through metadata engineering - Chisholm, Malcolm, 1953- (Boston : Morgan Kaufmann ; Oxford : Elsevier Science, 2004)
This is the only book that demonstrates how to develop a business rules engine. Covers user requirements, data modeling, metadata, and more. A sample application is used throughout the book to illustrate concepts. The code for the sample application is available online at http://www.refdataportal.com. Includes conceptual overview chapters suitable for management-level readers, including general introduction, business justification, development and implementation considerations, and more. This is the only book that demonstrates how to develop a business rules engine. Covers user requirements, data modeling, metadata, and more. A sample application is used throughout the book to illustrate concepts. The code for the sample application is available online at http://www.refdataportal.com. Includes conceptual overview chapters suitable for management-level readers, including general introduction, business justification, development and implementation considerations, and more.
What are business rules and business rules engines? -- Why build a business rules engine? -- Data modeling and database design -- Who defines business rules and when do they do it? -- The atomicity of business rules -- The black box problem -- The components of a business rules engine -- Populating table data in the repository -- Populating column data in the repository -- Populating relationship and subtype data in the repository -- Populating reference data in the repository -- Defining business processes and related information -- Extending the database -- Managing the database -- Implementing a simple business rule -- More edit validation rules, rule components, and rule versions -- Rule types for checking referential integrity -- Working with batch processes : setting indicators and reference data code values -- Implementing rule types using relationships and subtypes -- Rules with subtypes and business metadata -- Debugging in business rules engines -- Managing the business rules engine.
Includes index.
Includes bibliographical references (p. 471-472) index.
Keywords: Database management; Electronic books